Notes of the ’Visitation of the Pestilence’ from the Parish Records of South Leith, A.D. 1645, in connexion with the Excavations of large masses of Human Remains during the Drainage Operations at Wellington Place, Leith Links, A.D. 1861-2 - Robertson, D H (Proceedings of the Society of Antiquaries of Scotland, 1863)
After the discovery of human remains near Leith Links in the 1860s, D H Robertson dismissed arguments that these were the remains of battle casualties from the Siege of Leith. In this article, he instead argues that they are more likely to be victims of the plague outbreak in Leith from 1645. He presents some original documents that describe the situation and provides some death figures. On the day, he also presented a stone hammer and marine shells to the Society, found near the remains. Meeting notes for 10 February, 1862 are appended.